2016
DOI: 10.18632/oncotarget.11572
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical investigation of ibrutinib, a Bruton's kinase tyrosine (Btk) inhibitor, in suppressing glioma tumorigenesis and stem cell phenotypes

Abstract: Standard interventions for glioma include surgery, radiation and chemotherapies but the prognosis for malignant cases such as glioblastoma multiforme remain grim. Even with targeted therapeutic agent, bevacitumab, malignant glioma often develops resistance and recurrence. Thus, developing alternative interventions (therapeutic targets, biomarkers) is urgently required. Bruton's tyrosine kinase (Btk) has been long implicated in B cell malignancies but surprisingly it has recently been shown to also play a tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…20,99 For example, ibrutinib, a Bruton's tyrosine kinase inhibitor, is promising to target GSCs. 100 Furthermore, proteins involved in invasive behavior and therapy resistance of glioblastoma, such as TROY and SGEF, may well be overexpressed especially in GSCs which warrants further research with respect to specific therapeutic targeting of GSCs. 101,102 Alternatively, interactions between SDF-1α/CXCR4 and OPN/CD44 should be disrupted to enforce GSCs out of their protective niches to sensitize them to chemotherapy and irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…20,99 For example, ibrutinib, a Bruton's tyrosine kinase inhibitor, is promising to target GSCs. 100 Furthermore, proteins involved in invasive behavior and therapy resistance of glioblastoma, such as TROY and SGEF, may well be overexpressed especially in GSCs which warrants further research with respect to specific therapeutic targeting of GSCs. 101,102 Alternatively, interactions between SDF-1α/CXCR4 and OPN/CD44 should be disrupted to enforce GSCs out of their protective niches to sensitize them to chemotherapy and irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib has recently been shown to have an-tumor activity in some solid cancers [ 23 ]. More recently, BTK has been shown to also play a tumorigenic role in GBM and associate with its sphere-forming potential [ 24 ]. Consistent with the report, we found that ibrutinib can significantly inhibit the proliferation of glioma cells in vitro and in vivo through inducing G1 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that ibrutinib can be evaluated as novel therapeutic agent for glioma tumor. A recent study demonstrate that the combination of ibrutinib and temozolomide (TMZ) exert more inhibitory effect [ 24 ]. Thus, the combination of TMZ and ibrutinib may be a rational development of therapeutic approaches and clinical trials for glioma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of ibrutinib in solid tumors is currently being evaluated by a series of research teams including our own group [42][43][44]. However, the prognostic benefit of these molecular changes in patients with solid tumors is still unknown.…”
Section: Discussionmentioning
confidence: 99%